Growing Together: Assessing Equity and Efficiency in an Early-Life Health Program in Chile - Damian Clarke; Gustavo Cortés Méndez; Diego Vergara Sepúlveda (Institute of Labor Economics (IZA), 2018)
We study the mechanism of action of an early-life social safety net program, and quantify its impact on child health outcomes at birth. We consider both the equity and efficiency implications of program impacts, and provide a metric to compare various such programs around the world. In particular, we estimate the impact of participation in Chile Crece Contigo (ChCC), Chile's flagship early-life health and social welfare program, using administrative birth data matched to social benefits usage. We find that this targeted social program had significant effects on birth weight (approximately 10 grams) and other early life human capital measures. These benefits are largest among the most socially vulnerable groups, however shift outcomes toward the middle of the distribution of health at birth. We show that the program is efficient when compared to other successful neonatal health programs around the world, and find some evidence to suggest that maternal nutrition components and increased links to the social safety net are important mechanisms of action.
Keywords: H23; O15; I14; H43; O38; H51; 330; public health; neonatal health; social security; efficiency; early life investments